A leitura da linguagem humorística nas Tiras do Pessan - Santos, Everton Pereira (2021)
Comic strips require that the reader is able to read implicits that go beyond utterances. This type of reading occurs when the reader understands the linguistic-imagery aspects that generate humor in a situation of socio-communicative interaction. We observed, under the scope of Applied Linguistics, that the teaching of the reading of comic strips involves understanding the humor effects of the strips mobilized by the comic artist and the reader's role in their construction. In order to achieve this objective, we used theoretical and methodological subsidies from didactic engineering developed by Dolz (2016). In view of these constraints, we evidence conditions for carrying out a didactic transposition process with the genre comic strips, exploring the functioning of humorous language. Therefore, we analyzed comic strips based on devices developed in three theories of linguistic studies that contribute to the reading of the genre: the Logic of Conversation (GRICE, 1982) with the notion of implicature, that is, implicit information that needs to be calculated by another interlocutor; the Incongruence Theory (MORREAL, 1983) with the notion of breaking expectations of a social pattern that cause humor; and the General Theory of Verbal Humor (ATTARDO; RASKIN, 1991) with the notion of scripts: semantic fields evoked by a word or sentence and that cause humor when opposed. This research proposes, therefore, to analyze the reading of comic strips by bringing the studies of these three theories in order to point out possibilities for the analysis of comic strips, thus contributing to the studies of Applied Linguistics. In addition, the research carries out the preparation of a Workbook, exploring the language skills inherent in the construction of meaning in the reading of strips endowed with implicit in the dynamics of interaction that occur between the characters within the genre.